Positive Affect as a Source of Resilience for Women in Chronic Pain - Zautra, Alez J. (2005)
A sample of 124 women with osteoarthritis (OA) and/or fibromyalgia (FMS) completed initial assessments for demographic data, health status, and personality traits and 10 to 12 weekly interviews regarding pain, stress, negative affect, and positive affect. Multilevel modeling analyses indicated that weekly elevations of pain and stress predicted increases in negative affect. Both higher weekly positive affect as well as greater positive affect on average resulted in lower negative affect both directly and in interaction with pain and stress. Finally, increases in weekly negative affect and higher average negative affect related to greater levels of pain in subsequent weeks. In contrast, higher levels of overall positive affect predicted lower levels of pain in subsequent weeks.